Biomaterials based nano-applications of Aloe vera and its perspective: a review. Issue 105 (12th October 2015) - Balaji, Arunpandian; Vellayappan, Muthu Vignesh; John, Agnes Aruna; Subramanian, Aruna Priyadarshini; Jaganathan, Saravana Kumar; SelvaKumar, M.; Mohd Faudzi, Ahmad Athif bin; Supriyanto, Eko; Yusof, Mustafa
Abstract : In modern biomedical researches, the Aloe vera extract has been engaged in the synthesis of various micro and nanoformulations based smart structures, which increased its competence in wound healing, tissue engineering and drug delivery applications. Abstract : Aloe vera is noted for its meritable medicinal as well as commercial usages. From the past until now, it has been used as a promising remedy for several ailments. Recently, the concept of nanotechnology has astonishingly changed its outlook for biomedical applications. Nanotechnology has revolutionized several fields with its admirable capabilities and ground-breaking innovations. In the field of medicine, nanostructured materials have introduced a great range of flexibility by refashioning traditional practices and also by exploring new effective approaches. Accordingly, the usage of Aloe vera in the form of hydrogels, nanoparticles, nanocomposites, nanofibers and bio-inspired sponges has extended its well established application spectrum in the fields of wound healing, tissue engineering and drug delivery. In addition, the growing interest in consuming and synthesizing materials based on green or eco-friendly methods also highly encourages the use of numerous plant-based natural products including Aloe vera . Hence, an effort has been made to discuss the works related to recent advancements made in the use of Aloe vera, especially in the form of biomaterial-based nanostructures. This will encourage scientists to explore the unplumbed abilities of Aloe vera . Moreover, it will also help the industry players to recognise its immense potential and bring significant Aloe products to the market.